A ação docente do tutor a distância no curso de licenciatura em matemática do CESAD/UFS - Santos, Gláucia Dias (2017)
This study had the objective of analyzing how the tutors' teaching activity is done at e- learning in the Mathematics Degree Course at CESAD / UFS. As specific objectives, we were searching to understand how the tutor assists the students in the acquisition of specific knowledge, without exposing classes in the teaching process, as well as investigating the participation of the tutor in the evaluation process of student learning and, finally, present the participation of the tutor in the activities, as mediators and facilitators of learning. We have as main references the works of Valente (2010), Belloni (2008), Ferrete (2010), Moore (2008), Carvalho and Ritto (2010), Masetto (2013), Gil (2008 and 2010), Gouy And Mill (2010), as well as academic papers and official documents. For data collection, the use of a questionnaire with 12 open questions related to the central question was adopted. The analysis and interpretation of the data were based on the proposal of Bardin (1977), named Content Analysis. The questions were organized as categories, which are classified by the author as rubrics or classes. These gather a group of elements under a generic title, which are grouped by reason of the common characters of the elements. From the analysis of the data, it was possible to observe that although the tutors play such important roles in EaD and that their functions are similar to the functions of conventional teachers, there is still in the view of some tutors surveyed, the lack of definition of their functions as teachers, Because some tutoring is not teaching but an orientation to help the student in understanding the contents studied, it was also possible to observe that the teaching practice of these tutors is not exercised as established by the program and expected by them. The tutors pointed out that the main reason for not teaching in the way established by CESAD / UFS is the lack of interest of the students who do not seek them so that they can fully exercise their functions in the course in question, thus their actions as Teachers are being devalued.